Dynamic Analysis of a Rotating Cardan Shaft under the Influence of a Breathing Crack and Dense Fluid Force - Bernard Xavier Tchomeni Kouejou; Alfayo Anyika Alugongo (Shock and Vibration)
To extract any information from a complex data vibration, the time-frequency technique represents a suitable tool and a better indicator of the overall asset health of a rotating machine. Fluid influences on a cracked driveshaft and dynamic analysis of a rotating Cardan shaft are discussed in this paper. The study of the forced vibration signals of the rotating Cardan shaft focused uniquely on the impact of the hydrodynamic forces near the cracked driveshaft and its transmission of power to a driven shaft. By merging each subsystem consisting of the breathing crack mechanism in a rotating shaft, the perturbation function between misaligned shafts and transient hydrodynamic forces results in a strongly nonlinear system of partial differential equations, which becomes complicated when analyzing the dynamic response of the Cardan system. In view of the complexity of the Cardan system, the instantaneous frequency identification based on synchrosqueezing wavelet transform filters is numerically used to provide a reliable indication of the rotating system equipment’s health. A conclusive dynamic analysis through the wavelet synchrosqueezing demonstrated that the Cardan joint and the hydrodynamic resistance forces have a high impact on the system’s vibration characteristics and significantly influence the transmission motion with a continuous increase of the driven shaft vibration amplitudes.